Evaluation of factor VIII value in normal women and whom encountered recurrent pregnancy loss: is there any significant difference? - Rez, Douaa Al; Eldine, Hasan Naser; Alhalabi, Marwan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Recurrent pregnancy loss (RPL) is a serious problem on the women, it defined as two or more consecutive pregnancy losses before the fetus has reached birth. The aim of this study is to evaluate the association between the elevation in the factor VIII and RPL. Because women who have thrombophilia have increased risk of fetal loss in most studies. Methods: A total 72 women were recruited in this case control study. They divided into two groups: the RPL group included 41 women with a history of recurrent pregnancy loss and the control group included 31 healthy women, who had at least one successful pregnancy and none of them had a history of fetal loss or complicated pregnancy. Results: A majority of the patients of this study didn’t have a high level of factor VIII, 9 of 41 (22%) patients of RPL group in comparison with 21 of 32 (65,6%) of control group, that suffer from the increase rate of FVIII, this means that factor VIII doesn’t effect on RPL. Conclusions: The present study showed that the serum elevation in the factor VIII is not significantly associated with RPL.